A review on project management and issues surrounding dynamic development environment of ICT project: Formation of research area - Othman M.; Zain A.M.; Hamdan A.R. (2023)
This paper presents a review of methods, practices, and analysis on performance and challenges of Project Management for ICT projects with regards to accommodating change. Specifically, the main interest of the review is to understand the impact that is brought by the dynamic environment of projects developed today. The dynamic environment is synonymous to instability but the traditional project management approach favours a stable environment. The following were undertaken: 1. Review of the existing and popular standards, practices, and tools. 2. Study on reasons leading to project failures 3. Analyses of how much of these failures are connected to the dynamic/unstable/changing nature of the development environment. The undertakings lead to a high level solution proposal. It is hoped that the undertaking has formed a strong foundation for further research dedicated at improving project management approach of ICT project development given an unstable environment.